ДЕКОНСТРУКЦИЯ ФЕНОМЕНА ОТЦОВСТВА В СВЯЗИ С ТРАНСФОРМАЦИЯМИ НОРМАТИВНОЙ МУСКУЛИННОСТИ - Коробкина, Т. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
Статья посвящена малоизученному феномену отцовства. Рассматриваются процессы деконструкции феномена отцовства в связи с трансформациями нормативной модели маскулинности. Проанализированы различные аспекты категогии маскулинности, традиционные типы отцовского поведения и перспективы их развития в посттрадиционном обществе. Т.В. Коробкіна ДЕКОНСТРУКЦІЯ ФЕНОМЕНУ БАТЬКІВСТВА У ЗВ’ЯЗКУ З ТРАНСФОРМАЦІЯМИ НОРМАТИВНОЇ МУСКУЛИННОСТИ Стаття присвячена маловивченому феномену батьківства. Розглядаються процеси деконструкции феномену батьківства у зв’язку з трансформаціями нормативної моделі маскулинности. Проаналізовані різні аспекти категогии маскулинности, традиційні типи батьківської поведінки і перспективи їх розвитку в посттрадиційному суспільстві. Ключові слова : батьківство, маскулинність, «традиційний батько», «відсутній батько», «відповідальний батько», «новий батько». T. Korobkina DECONSTRUCTION OF THE PHENOMENON OF FATHERHOOD IN CONNECTION WITH TRANSFORMATIONS OF NORMATIVE MASCULINITY This article is dedicated to phenomenon of fatherhood. Processes of deconstruction of phenomenon in connection with transformations of normative masculinity are considered. Different aspects of category of masculinity, traditional types of father’s behavior and perspectives of their development in post traditional society are analyzed. Key words: fatherhood, masculinity, “traditional father”, “absentee father”, “responsible father”, “new father”.